2-hydroxyethylammoniumsulfate ionic liquid performance as simultaneous fuel and sulfating agent in tablet-like manganese and iron incorporated titania synthesis: Biodiesel production from waste oil. (15th May 2023) - Bekhradinassab, Ensie; Tavakoli, Akram; Haghighi, Mohammad; Shabani, Maryam
Research highlights: Three newly proposed ionic liquids, including 2-hydroxyethylammonium acetate (ILA), 2-hydroxyethylammonium formate (ILF), and 2-hydroxyethylammonium sulfate (ILS), were investigated as fuel in the solution combustion process. A highly acidic manganese and iron-incorporated titania was synthesized. 2-hydroxyethylammonium sulfate (ILS) led to the creation of a very capable catalyst that produced biodiesel from waste oil with a high reaction rate. Abstract: The efficient tablet-like manganese and iron incorporated titania catalyst was synthesized in the presence of 2-hydroxyethylammonium sulfate (ILS) as both fuel and sulfating agent via microwave for biodiesel production. Catalyst characterizations were conducted by XRD, FESEM, EDX, BET-BJH, and TPD-NH3 analyses. The catalyst was also synthesized via other fuels including urea, 2-hydroxyethylammonium acetate (ILA), and 2-hydroxyethylammonium formate (ILF). The nature of fuels affected the catalyst's physicochemical properties and performance. Urea created a large portion of wide pores in the catalyst. ILS led to the creation of a highly acidic catalyst with an acid density of 0.804 mmol/m 2 . Oleic acid conversion for catalysts synthesized by urea, ILA, ILF, and ILS in the condition of 110 °C, 1.5 h, 9 wt% catalyst, alcohol to oil mole ratio of 20 was 63.5, 39.36, 48.56, and 93.11 %. MnFeTi(ILS) showed a good capability for producing biodiesel from sunflower (92.12 %) and waste oil (91.43 %). The catalyst was reused 5 times, and only a 6 % conversion loss was detected.